PENGARUH PRICE DISCOUNT FRAMING DAN NEED FOR COGNITION TERHADAP ATTITUDE DAN INTENTION KONSUMEN DALAM MEMBELI TIKET KONSER MUSIK (STUDI KASUS PADA KONSER MUSIK HARMONICA 2016) - Humaerah, Aisyah (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to determine the effect of framing the discount price and need for cognition on consumer attitudes and intentions in buyingtickets for a concert. This type of research is an experimental research. Participants in this study were 200 people who had bought tickets formusic concerts that is divided to four experimental group . The primary data used in this study were collected through questionnaires. MANOVAused to test the effect of independent variables of the study (price discount of framing and need for cognition) on the dependent variableof the study (attitudes and intentions of consumers in buying).The conclusion that can be drawn from the results of this study areprice discount framing no effect on attitudes and intentions in buyingtickets for a concert, need for cognition influence the attitudes andintentions of consumers in buying tickets for a concert and there is nointeraction between the discount price of framing and need for cognition on the attitudes and intentions of consumers in buying tickets for aconcert. Therefore, it is important for a marketer to pay attention onmessagesÂ  framing in an ad discounts in order to influence the attitudesand intentions of consumers. In addition, marketers are also required tobe more selective in entering information into a message and adapt the content of message to the characteristics of consumers to convinceconsumers in improving attitudes and intentions.Keywords: Price Discount Framing, Need for Cognition, Attitude,Intention, Music Concert